Integrating Games in Teaching Maritime English: A Collaborative Auto-Ethnographic Inquiry - Herdawan, Deri; Sari, Dhesi Wulan; Marselia, Marselia; Rahayuningsih, Mahsunah Etik (Universitas Islam Negeri Raden Intan Lampung, 2024)
English for Specific Purposes (ESP) has been getting attention as it puts a strong emphasis on specific language needs in various professional and academic settings, meeting the current trend of English education. As a sub-field of ESP, Maritime English (ME) is taught to students who are projected to be involved in the maritime industry. The present study explored the journey of teachers in integrating game-based learning to teach ME. Specifically, it investigated what teachers experienced in teaching ME, how teachers integrated games into teaching ME, and what challenges teachers faced in integrating games into teaching ME. A Collaborative Auto-Ethnographic Inquiry design was implemented in this qualitative study. The data were sourced from the four authors as we shared our experience in teaching from the first time we taught ME. The necessary data were collected through narrative inquiry, photo voice, and semi-structured interviews, followed by a thematic data analysis. The findings revealed challenges that were faced in teaching ME before and after integrating games. Through the discussion, we highlighted how professional teachers should prepare for the class and adapt to the situation in the class.